Self-management education programs for age-related macular degeneration: A systematic review - Lee, L.; Packer, Tanya; Tang, S. H.; Girdler, Sonya (Wiley-Blackwell Publishing, 2008)
Objective: To review the effectiveness of education programs to improve emotional status, daily living and self-efficacy in adults older than 60 years with age-related macular degeneration (AMD). Method: Electronic searches of three databases and manual searches of references lists located randomised controlled trials (RCTs) and quasi-experimental studies. Health education programs aimed at increasing knowledge of AMD, skills training or behavioural change were included. Data extraction and quality assessment were undertaken by two reviewers. A narrative analysis was possible. Results: Three protocols were reported in four studies (n= 532) with three follow-up studies – all contained elements of self-management programs. Effect sizes for the three outcomes ranged from small to very large (0.14–1.21). Conclusions: Self-management programs appear effective for older adults with AMD. Small sample size, use of nontraditional statistics and methodological quality meant only a narrative analysis was possible. Future studies with more robust methodology including intent-to-treat analysis are still required.